2011
DOI: 10.1242/jcs.080523
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytically cleaved MLL subunits are susceptible to distinct degradation pathways

Abstract: The mixed lineage leukemia (MLL) proto-oncogenic protein is a histone-lysine N-methyltransferase that is produced by proteolytic cleavage and self-association of the respective functionally distinct subunits (MLLN and MLLC) to form a holocomplex involved in epigenetic transcriptional regulation. On the basis of studies in Drosophila it has been suggested that the separated subunits might also have distinct functions. In this study, we used a genetically engineered mouse line that lacked MLLC to show that the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 72 publications
3
54
1
1
Order By: Relevance
“…16 The first and fourth PHD fingers function together with the phenylalanine/tyrosine-rich (FYRN) domain to mediate the intramolecular interaction between MLL N and MLL C . 47 In our experiments, inclusion of the bromodomain is sufficient to mediate the interaction with ASB2, whereas the addition of PHD4 enhances binding (Figure 3). Several bromodomains have been demonstrated to mediate protein-protein interaction through recognizing acetylated lysines.…”
Section: Discussionmentioning
confidence: 55%
“…16 The first and fourth PHD fingers function together with the phenylalanine/tyrosine-rich (FYRN) domain to mediate the intramolecular interaction between MLL N and MLL C . 47 In our experiments, inclusion of the bromodomain is sufficient to mediate the interaction with ASB2, whereas the addition of PHD4 enhances binding (Figure 3). Several bromodomains have been demonstrated to mediate protein-protein interaction through recognizing acetylated lysines.…”
Section: Discussionmentioning
confidence: 55%
“…A knockin allele lacking the SET domain of the Mll gene resulted in reduced Hoxc8 expression and a decreased amount of mono-methylated histone H3 lysine 4 modification at the Hoxc8 locus in embryos [37]. However, this mouse line was viable after birth, unlike other Mll-deficient mouse lines [16,17,29]. No differences in Hoxa9 expression and repopulating potential were observed in the cells of the LSK fraction (containing HSCs and MPPs) from SET domain-deficient mice compared to the wild-type animals [38].…”
Section: Introductionmentioning
confidence: 94%
“…Posterior Hoxa genes facilitate the expansion of immature hematopoietic progenitors [28], suggesting that MLL drives the proliferation of immature hematopoietic cells by upregulating posterior Hoxa genes. Studies of Mll-knockout mice have confirmed its requirement in the hematopoietic lineage of both adult and fetal hematopoietic systems [17,24,29,30]. Mll-deficient embryos produce a smaller population of hematopoietic stem cells (HSCs), MPPs, common myeloid progenitors (CMPs) and granulocyte-macrophage progenitors (GMPs) in the fetal liver than in the control [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H3K4 trimethylation (H3K4me3) catalyzed by MLL activates transcription, leading to orchestrated upregulation of key developmental genes, such as Hox genes (23,24,26,27). Notably, the activity of MLL is modulated by posttranslational modifications, such as phosphorylation, ubiquitination, and proteolysis (20,21,28,29). MLL undergoes site-specific proteolytic cleavage by taspase-1 (encoded by TASP1), which gives rise to a mature 500-kDa MLL N320/C180 heterodimer (28).…”
Section: Introductionmentioning
confidence: 99%